Pesan Komunikasi Profetik Ustad Rahmat Najieb Dalam Membangun Kesadaran Beribadah di Masjid PP Desa Cipagalo - Nasira, Muhammad Mufti Sulthanan (Prophetica : Scientific and Research Journal of Islamic Communication and Broadcasting, 2019)
The aim of this research is to determine the prophetic communication messages used by Ustad Rahmat Najieb in building awareness of worship among the congregation at the PP Mosque. The research method used is qualitative, with a descriptive approach, data collection techniques in the form of interviews, observation and documentation. The results of this research are that the prophetic communication messages carried out by him at the PP Mosque have three types of messages seen from the aspect of the method delivered in the form of al-hikmah in the form of a story, mauidzhah hasanah in the form of advice, and al-mujaida in the form of a discussion which is applied through the study of the book Tafsir Ibnu Katsir , Tafsir An-Nur and the fiqh book Bulughul Maram in building awareness of worship.